2018
DOI: 10.1016/j.fitote.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analytical assets aid botanical authenticity and adulteration management

Abstract: This article reviews and develops a perspective for the meaning of authenticity in the context of quality assessment of botanical materials and the challenges associated with discerning adulterations vs. contaminations vs. impurities. Authentic botanicals are by definition non-adulterated, a mutually exclusive relationship that is confirmed through the application of a multilayered set of analytical methods designed to validate the (chemo)taxonomic identity of a botanical and certify that it is devoid of any a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 111 publications
0
69
0
2
Order By: Relevance
“…supply of many species that are harvested from the wild (Coghlan et al, 2015) is stimulating the economicallymotivated adulteration (EMA) (Simmler et al, 2018). It was recently reported that 27% of almost 6,000 commercial herbal products sold in 37 countries were found to be adulterated, while in Europe almost half (47%) were adulterated.…”
Section: The Raw Plant Materials and Its Influence On The Authenticitymentioning
confidence: 99%
“…supply of many species that are harvested from the wild (Coghlan et al, 2015) is stimulating the economicallymotivated adulteration (EMA) (Simmler et al, 2018). It was recently reported that 27% of almost 6,000 commercial herbal products sold in 37 countries were found to be adulterated, while in Europe almost half (47%) were adulterated.…”
Section: The Raw Plant Materials and Its Influence On The Authenticitymentioning
confidence: 99%
“…[12][13][14] The often incomplete and/or conflicting information on mechanisms of action, appropriate uses, and expected health effects poses challenges for formulating hypotheses and designing CT. [12][13][14] The often incomplete and/or conflicting information on mechanisms of action, appropriate uses, and expected health effects poses challenges for formulating hypotheses and designing CT.…”
Section: Challenges To Be Addressedmentioning
confidence: 99%
“…ex DC differ significantly in the ratio of liquiritigenin to isoliquiritigenin, as well as in congeneric constituents, and are therefore expected to have different bioactivities. 14,124 Descriptions of approaches to NP selection and characterization have been published recently. 15,124 Identity and purity of all materials used, regardless of the supplier, should be verified prior to use.…”
Section: Np Specifications and Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization sufficient for the detection of such minor components, known or unknown, is therefore critical for quality control and for monitoring batch-to-batch variation and stability (14,124). Identity and purity of all materials used, regardless of the supplier, should be verified prior to use (13,124). Descriptions of approaches to NP selection and characterization have been published recently (15,125,126).…”
Section: Np Characteristics Critical For Replicability Np Specificatimentioning
confidence: 99%